(untitled) (Journal of Medicine, 2010)
This study was carried out in a private Intensive Care Unit (ICU) to assess the psychiatric morbidities and major psychiatric problems in patients requiring ICU. The most common psychiatric diagnosis was found to be Depressive disorder followed by attention seeking behavior. Chemicals (organophosphorous, kerosene and other medicine) were the most frequent agent used among suicide attempt patients. Keyword: Deliberate self harm, intensive care, mood disorders DOI:10.3329/jom.v11i1.4260 J Medicine 2010: 11: 7-11